Antiphosphatidyl Serine Autoantibodies and Premature Coronary Events - Ali, Hisham Y M (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2007)
OBJECTIVES: To determine whether antiphosphatidyl serine autoantibodies (aPS) are associated with increased risk of occurrence of coronary events in selected patients. METHODS: This study compared 50 patients with coronary events with 30 controls, recruited from the cities of Mosul, Erbil, and Dohuk cities, Northern Iraq, between March 2004 and March 2005. The patient group consisted of 23 individuals with myocardial infarction and 27 with angina. We evaluated the presence of aPS antibodies (IgG and IgM isotypes) by an enzyme-linked immunosorbent assay. The studied cases were less than 50 years of age (mean ± SD, 39.6 ± 5.9) and had no recognizable risk factors. RESULTS: The frequency of detecting IgG aPS was 10/50 (20%) among patients and 1/30 (3.3%) among controls, with significant difference and with adjusted odds ratio (OR) of 3.2 (95%CI, 1.1–9.1; p < 0.05). The IgM aPS frequency was 3/50 (6%) among patients and zero in the controls, with non-significant difference. The three cases were also IgG positive (i.e. the frequency rate for detection of aPS of IgM was the same as for IgG). Moreover, this marker (aPS) was detected in 8/12 (66.7%) of cases with unstable angina, in 2/15 (13.3%) with stable angina, and in none of the cases with myocardial infarction. CONCLUSION: IgG aPS autoantibodies are associated with increased risk of coronary events especially angina of unstable subset.